TRANSFORMATION OF THE MANAGEMENT OF THE HAJJ DAM FROM MAKKAH TO INDONESIA: A REVIEW OF MAQASHID SHARIA ON THE FATWA OF MUI AND MUHAMMADIYAH - Muhammad Fikri; Ishak Hariyanto (Academic Bright Collaboration, 2026)
This study examines the transformation of Hajj dam (penalty sacrifice) management from Mecca to Indonesia through a maqashid al-shari‘ah analysis of the fatwas issued by the Indonesian Ulama Council (MUI) and Muhammadiyah. During the period 2025–2026, a significant shift has occurred in contemporary Islamic legal discourse regarding the location of dam slaughter for tamattu‘ and qiran Hajj, amidst the institutional transformation of Indonesia’s Hajj governance following the enactment of Law Number 14 of 2025. Using a qualitative-normative approach with comparative-fatwa analysis, this study places MUI Fatwa Number 41 of 2011, which prohibits slaughter outside the Sacred Precincts, and the Muhammadiyah Tarjih Council’s 2026 fatwa, which permits it under three conditions, as the primary objects of investigation. The findings indicate that MUI’s fatwa emphasizes textual-ritual aspects by prioritizing spatial authority as an integral part of the pilgrimage rituals, while Muhammadiyah’s fatwa employs a maslahah-contextual approach emphasizing the universal objectives of shari‘ah, particularly the protection of property (hifz al-mal), life (hifz al-nafs), and environment (hifz al-bi’ah). From a maqashid al-shari‘ah perspective, the transformation of dam management to Indonesia does not yet possess a strong legal rationale (‘illah) for relocation; therefore, this study recommends the necessity of i‘adatu al-nazhar (re-examination) of the Muhammadiyah fatwa that permits the management of dam in Indonesia. This study is original in that it provides a comparative maqashid al-shari‘ah analysis of the MUI and Muhammadiyah fatwas on the relocation of Hajj dam slaughter to Indonesia, situating the debate within the contemporary transformation of Indonesia’s Hajj governance after Law Number 14 of 2025.